NILAI TAUHID KEARIFAN LOKAL REPRESENTASI PENGEMBANGAN DESA WISATA RELIGI DI MAKAM GUS MIEK - Sujarwoko; Agan, Subardi; Sasongko, Sempu Dwi (STKIP PGRI Ponorogo Press, 2021)
It is important to develop a study of local wisdom. This is related to the development of religious tourism villages where each region has its own characteristics in creating policies for its region. In Ngadi Village, Mojo Subdistrict, Kediri Regency, there is a central figure who even though he has passed away, his advice is still carried out by the local community and even people outside the region, either as written in his essay or conveyed verbally when he is still alive. The figure referred to as waliyulloh is none other than Kiyai Hamim Tohari Djazuli or better known as Gus Miek. This study used a qualitative descriptive approach with the researcher as an instrument. The concepts of tawhid used in this study include: a) mahabbah, b) tawaduk, and c) tawakal. The results and discussion show that: mahabbah or Gus Miek’s divine love can be seen from the nature that is owned by the term jadzab, in the Javanese language gandrung, the madness of his love for the servant of Allah. The tawaduk owned by Gus Miek can be seen from his simple nature in his behavior even though he is the son of a great kiyai and the founder of the Islamic boarding school. Gus Miek’s tawakal can be seen from his submissive behavior to Allah’s will that happens to him and his family.